Lightweight concrete from incineration ash - Lim, Kok Hua. (2008)
In recent years, Singapore has to cope with the increasing amount of municipal solid waste (MSW) generated by her population through incineration. As land is scarce and landfills are fast dwindling in Singapore, the incineration ashes that are produced in huge amounts faces the challenge of safe and proper disposal. One viable solution to the disposal problems would be the reuse of MSW fly and bottom ash for civil engineering applications. The dilemma of how to effectively and safely dispose of this waste had led to the investigation on the possibility of using these wastes in making incineration ash based non-conventional concrete products such as lightweight fibre-reinforced hollow block wall panels. It is the aim of this project to develop a new binding matrix consisting of MSW incineration fly and bottom ashes, cement and additives like fibres and lightweight materials, which will ultimately serve as non load-bearing interior wall partitions. Mix design was carried out to determine the optimal mixture to enhance the physical properties of the new binding matrix and to effectively immobilize heavy metals from leaching. Inorganic fibre was added to enhance the flexural capacity of the end product.